Optimization of Tambourine Kecer Punching Machine with Two Axis Movement System using Trimmer Machine to Improve Efficiency and Product Quality - Lostari, Aini; Rian, Novi Indah; Amal, Fairus Ikhlasul (Universitas Muhammadiyah Jakarta, 2023)
Indonesian traditional arts, such as tambourine art, have become an inseparable part of cultural heritage. In Kaliwot Village Bungah Gresik, the process of making tambourines still relies on manual methods, especially at the stage of punching the kencer with a hand saw. As a result, the tambourine produced has a rough and uncomfortable surface. This research aims to improve the efficiency and quality of tambourine production through the design of a kecer punching machine using a trimmer machine. The experimental research involved designing, manufacturing, and testing the trimmer machine, focusing on the timing of tambourine kencer punching. The types of wood used include mango, jackfruit, and mahogany. The results included a drive engine power of 0.35 kW, a plan power of 0.45 kW, and variations in motor torque: mahogany 0.0197 Nm, jackfruit 0.0215 Nm, mango 0.0184 Nm. The average hollowing time ranges from 9.42 to 13.31 minutes, with a daily production capacity of 35-42 tambourine seeds, depending on the type of wood. Analysis of motor torque showed that higher motor revolutions increased torque during feeding, potentially affecting wood hardness. The conclusion of the study emphasizes that the use of a trimmer machine can increase the efficiency and production capacity of tambourines, making a positive contribution to the craftsmen in Kaliwot Village as well as the preservation of tambourine art as a whole.